Personality, long-term stress, and acute stress reactions to mental workload - Niemi, Katri (My University, 2021)
Physiological stress reactions can be studied using various methods, like measuring heart rate, blood pressure or brain activation. Those methods reveal whether a situation is stressful or not and some of them might even distinguish mild stress from severe stress. However, not all people react identically to the same stimulus as there are individual differences in how things are perceived. This study focuses on the relations between personality, long-term stress, and acute stress reactions to mental workload. With 98 participants, the aim of this study was to examine (1) whether physiological measures (plasma cortisol, plasma noradrenaline, systolic blood pressure, diastolic blood pressure, low-frequency heart rate, high-frequency heart rate, and low-frequency / high-frequency ratio) of acute stress reaction induced by mental workload are related to subjectively assessed personality and long-term stress in a student-based population, and (2) if those connections exist, whether long-term stress or some personality traits (neuroticism, extraversion, openness, agreeableness, conscientiousness) alone or combined are more closely associated with observed physiological acute stress reactions than others. The participants performed a total of four sets of computer-based mental workload tasks; physiological stress reactions were measured during and after the tasks using cardiac and hormonal measures. Personality (Short Five, 60-item version) and long-term stress (The Perceived Stress Scale, 10-item version) were subjectively assessed. The Pearson correlation coefficients were computed between personality, long-term stress, and physiological stress measurements. Based on the correlation coefficients, the final examination was conducted by stepwise regression models. A combination of higher extraversion and conscientiousness, greater long-term stress and lower agreeableness accounted for one fourth in increased cortisol secretion, while extraversion alone explained less than 8 % of the variance in cortisol. The results regarding the heart rate variability measurements indicate that lower scores in conscientiousness were consistently associated with greater stress reactions: increased low-frequency/high-frequency ratio when performing visual and auditory serial recall tasks along with decreased high-frequency and increased low-frequency during N-back tasks. However, no relations between neuroticism or openness and acute physiological stress reactions occurred. These findings indicate that instead of a single trait, a combination of traits could provide a better explanation for why some tasks induce stress for some people but not for others. Future studies should focus on more consistent methods in personality assessments, stress induction and the use of physiological measures.
Keywords: Mental workload, personality, long-term stress, acute stress reactions